FRICTION IN ASCENDING GAS-LIQUID FLOW IN THE CHANNEL WITH CHAOTIC NOZZLE - E. A. Lapteva; E. Yu. Stolyarova; A. G. Laptev (Известия высших учебных заведений: Проблемы энергетики)
The approach determining the shear stress at the interface. As an example chosen gazliftovaya pipe. The tube is filled with fine chaotic showerheads. Nozzle is used for intensification of heat and mass transfer processes, and thus for the calculation of the efficiency of transport phenomena theoretically necessary to determine the shear stress at the interface/ For this purpose, values of the average volumetric rate of energy dissipation.